Development of a Computerized Adaptive Test for Problematic Mobile Phone Use - Liu, Xiaorui; Lu, Hui; Zhou, Zhao; Chao, Miao; Liu, Tour (Frontiers in Psychology, 2022)
Great number of mobile phone users in the world has increased in recent years. More time spent on phone, more negative effects, such as problematic mobile phone use. Many researchers have devoted themselves to revised the tools to measure problematic mobile phone use better and more precisely. Previous studies had shown that these tools have good reliability and validity, but most of them have some shortcomings because which was traditional paper-and-pencil tests based on Classical Test Theory (CTT). This study based on Item Response Theory (IRT) in order to solve these shortcomings, developed a Computerized Adaptive Testing for problematic mobile phone use (CAT-PMPU) and discussed the performance of CAT-PMPU. Then, used real data to simulate CAT, the measurement accuracy and reliability between paper-and-pencil test and CAT-PMPU were compared under the same test length. The results showed that CAT-PMPU was better than paper-and-pencil test in all aspects, it can reduce the number of items and improve the measurement efficiency effectively. In conclusion, the CAT-PMPU was developed in this study has good reliability, it provided a novel technical support for the measurement of problematic mobile phone use. It had a good application prospect.